“USAHA BAKSO IKAN” PADA KELOMPOK MAJELIS TAKLIM NURUL UKHUWAH DI DESA BORIKAMASE, KEC. MAROS BARU. KAB. MAROS - Nurjannah, Nurjannah (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2020)
Meatballs are a type of food that is loved by all people, old and young, as well as children. Fishmeatball business is an alternative food that is favored by all elements of society and has abusiness prospect that can target all people at an affordable price with materials that are easilyavailable and inexpensive, besides that the location of the business placement has a promisingeffect for business and organizational development. Generally processed meatballs from beef,while Borikamase Village, a fish producer in Maros district. The purpose of this program MTNurul Ukhuwah is equipped with skills to process fish balls and their marketing, so that in additionto serving in families with healthy meatballs with processed fish, it is also expected to increase theincome of families and organizations of majelis taklim. The approach taken begins withsocialization to build the same perception, training in making Fish Meatballs, training in startingand building a business, training in marketing techniques, it is expected that 100% of themanagement and members of MT have Fish Meat processing skills and more than half ( 50%)members formed a joint business Fish Meatballs as one type of group business to help theeconomy of members and organizations.